Association between long-term care and chronic and lifestyle-related disease modified by social profiles in community-dwelling people aged 80 and 90; SONIC study. (March 2019) - Kiyoshige, Eri; Kabayama, Mai; Gondo, Yasuyuki; Masui, Yukie; Ryuno, Hirochika; Sawayama, Yasuka; Inoue, Takako; Akagi, Yuya; Sekiguchi, Toshiaki; Tanaka, Kentaro; Nakagawa, Takeshi; Yasumoto, Saori; et al.
Highlights: Social profiles were categorized into two social sub-groups by latent class analyses. Relations of diseases with LTC were significant regardless of the social sub-group. The relations were not modified by the social sub-groups except osteoporosis. Abstract: Background: Chronic and lifestyle-related diseases and social status were reported to be associated with long-term care (LTC). The social factors should be treated as social sub-groups of which characteristics show social profiles. However, few previous studies considered that. The present study aimed to investigate the associations between LTC and chronic and lifestyle-related diseases, and whether the associations were modified by the social sub-groups in the community-dwelling elderly. Method: A cross-sectional study was conducted among 1004 community-dwelling participants aged 80 and 90. LTC was used as the outcome. Chronic and lifestyle-related diseases (i.e., stroke, heart disease, joint pain, osteoporosis, lung disease, cancer, hypertension, dyslipidemia, and diabetes) were used as the predictors. Education, household income, residential area, and support environment were analyzed by latent class analysis (LCA) to derive social profiles. We obtained odds ratios (ORs) of LTC from those diseases and tested interactions between those diseases and the social profiles by logistic regression analyses. Result: The participants were categorized into two sub-groups of social factors (n = 675 and 329) by LCA. Logistic regression analyses showed ORs (95% CI) of LTC were 4.69 (2.49, 8.71) from stroke, 2.22 (1.46, 3.38) from joint pain, 1.99 (1.22, 3.25) from osteoporosis, and 2.05 (1.22, 3.40) from cancer adjusting for the social sub-groups. There were no significant interactions between the social subgroups and those diseases in relation to LTC except for osteoporosis. Conclusion: The associations between LTC and chronic and lifestyle-related diseases were significant with adjusting for the social sub-groups, and not modified by that except osteoporosis.